2023
DOI: 10.3390/ijerph20053848
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations and Clinical Outcomes of Patients with COVID-19 in the Aseer Region, Saudi Arabia

Abstract: COVID-19 patients also present with rheumatological problems, cardiac problems, and even neurological manifestations. However, the data are still insufficient at present to fill the gaps in our understanding of the neurological presentations of COVID-19. Therefore, the present study was undertaken to reveal the various neurological manifestations of patients with COVID-19 and to find the association between neurological manifestations and the clinical outcome. This cross-sectional study was conducted in Abha, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
1
1
Order By: Relevance
“…Some studies have shown that outcomes were worse and ICU admissions were higher in those with neurological manifestations and/or complications than in those without neurological manifestations/complications, [10–13] which contrasts with this study. The contrasting results in these previous studies might be due to the presence of established neurological predictors of poorer outcomes more frequently than in our study; for example, in the study by Cho et al, 20% of patients had altered mental status.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that outcomes were worse and ICU admissions were higher in those with neurological manifestations and/or complications than in those without neurological manifestations/complications, [10–13] which contrasts with this study. The contrasting results in these previous studies might be due to the presence of established neurological predictors of poorer outcomes more frequently than in our study; for example, in the study by Cho et al, 20% of patients had altered mental status.…”
Section: Discussioncontrasting
confidence: 99%
“…Some articles have broadly (without looking into specific neurological manifestations or complications) described neurological manifestations as important predictors of worse outcomes, including mortality. [10][11][12][13] Other studies have focused on particular neurological manifestations and complications and found altered mental status and stroke to be the major neurological conditions associated with COVID-19 to predict worse outcomes and mortality in COVID-19 patients. [14][15][16] This article aims to discuss the neurological manifestations of COVID-19 and their association with outcomes in patients admitted to the Tribhuvan University Teaching Hospital, representing the first study of its kind in Nepal.…”
Section: Introductionmentioning
confidence: 99%